An Evaluation of Healthy Lifestyle Behaviors of Medical School Students - Cüneyt ARDIÇ; Nehir TAŞKIN (Bezmiâlem Science, 2018)

(untitled)
Objective:The aim of the present study was to evaluate healthy lifestyle behaviors of medical school students attending Recep Tayyip Erdoğan University during academic year 2016-2017.Methods:Among 510 students attending Recep Tayyip Erdoğan University during academic year 2016-2017, 285 were enrolled as volunteers in this study. A questionnaire form that was developed through literature information including sociodemographic characteristics as well as Healthy Lifestyle Behaviors Scale (HLBS) was used for data collection. Data analysis was performed through t-test, variance analysis, Mann-Whitney U, Kruskal-Wallis variance analysis.Results:Average age of the participants was 21-23 years. Mean scale score of the students was at moderate level with 127.38±19.28. The title of the subtopic with the highest score was “Self-realization” (25.19±4.89), whereas the lowest score was detected on “Physical Activity” (18.88±4.49). Female sex and improved awareness on health status were found to be associated with a healthy lifestyle attitude.Conclusion:The improvement of health developing attitudes of medical school students who are future healthcare professionals as well as role models for the community is important for public health. In line with these outcomes, planning and implementation of training programs regarding the topics that the students found unsatisfying in terms of health behaviors are essential.